Structure and Functional Role of Bacterial CRISPR System - A. V. Shashkova; A. A. Goryaev; N. I. Smirnova (Проблемы особо опасных инфекций, 2011)
Presented is the review of literature data on the recently discovered system of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR), which takes part in the defense against penetration of alien genetic information in prokaryotes. CRISPR structural peculiarities and functions, and putative mechanism of action are described. Also presented are data on the availability of this system in particularly dangerous infections agents and on the possibility of its application for molecular typing.